CEMAS TAK SELALU BURUK: PERAN ECO ANXIETY TERHADAP PERILAKU PRO LINGKUNGAN PADA ANAK MUDA JAKARTA - Salsabila Yasinda, Afifah; Rizki Wulandari, Indah; Waldah, Alysah (Psikologi UHAMKA, 2023)
Some of the problems that exist in big cities, especially DKI Jakarta, are poor air quality, many polluted rivers, not rooted in flood management to the problem of waste. The National Waste Management Information System (2022) shows that the amount of waste in DKI Jakarta every day is around 8,527.07 tons, and in one year the waste in DKI Jakarta reaches 3,112,381.40 tons. In addition to increasing the ecological burden, the increasing waste problem can also cause physical problems that can have an impact on mental health or commonly referred to as eco anxiety (Clayton, 2020). This study aims to determine the role of eco anxiety on pro-environmental behavior (PEB) in early adult communities from various regions in Jakarta. The temporary research assumption is that eco anxiety plays a role in pro-environmental behavior (PEB) in Jakarta's early adult community (18-25 years old). The sample used as participants is the early adult age community in Jakarta totaling 147 participants (m age = 23 years, male = 46). The research was conducted using quantitative non-experimental methods and data collection was taken using accidental sampling techniques by distributing online questionnaire links on various social media channels. The eco anxiety variable was measured using the Eco Anxiety Scale (Hogg et al., 2021) consisting of 13 items with a Cronbach alpha value of 0.921 (has good reliability), while pro-environmental behavior (PEB) was measured using the Environmental Action Scale (Alisat & Riemer, 2015) consisting of 18 items with a Cronbach alpha value of 0.960 (has good reliability). The results of this study can be used by practitioners engaged in the field of Social and Environmental Psychology as supporting information and knowledge, especially in designing interventions or persuasion programs to encourage pro-environmental behavior (PEB), the results of this study can also enrich the literature review of eco anxiety variables and pro-environmental behavior (PEB).